The effectiveness of acceptance and commitment therapy (ACT) on quality of life of women with chronic low back pain - Mousavi, Seyedeh Maryam; Kraskian Mujembari, Adis; Hassani Abharian, Peyman; Pashang, Sara (Researcher Bulletin of Medical Sciences, 2019)
Introduction: Acceptance and commitment therapy [ACT] can enhance psychological flexibility and subsequently improve mental health and quality of life of individuals. Also recovery of patients with chronic low back pain (LBP) is depended on several physical and psychological factors. Therefore, the authors aimed to examine the effectiveness of acceptance and commitment therapy (ACT) on quality of life of women with chronic low back pain. Method: It was a semi-experimental research with pre-test and post-test design together with control group. Participants were 14 women with chronic low back pain attending clinical centers and hospitals of Rasht who were selected by convenience sampling. Next, they were randomly assigned to experimental (ACT+ usual medical care) and the control group (usual medical care only).Then experimental group received ACT for 8 one-hour sessions. To analyze the data, covariance analysis was used. The instrument was self-reported by the World Health Organization's quality of life. Data analysis was performed using analysis of independent t-test. Results: Results indicated reduction effect in pain severity in the patients who practiced 8 sessions ACT reported significantly lower pain than patients who only received usual medical care. Also, the results shows that except of subscale of physical health (P < 0.38) there was significant increase in all other subscales of quality of life in experimental group (P < 0.001). Conclusion: The results show that acceptance and commitment therapy reduces pain severity and improve the quality of life and recommend use of coping strategic with pain in patients with chronic low back pain (CLBP). Counselors and family therapists recommended a counseling centers and family education classes in order to improve quality of life of female patients with CLBP.